Occurrence of selected antiphospholipid antibodies in offspring born from mothers with autoimmunity - Mocková, A; Ulčová-Gallová, Z; Náhlovský, J; Lukášová, V; Dort, J; Bibková, K; Micanová, Z (Lupus, 2012)
Autoimmune diseases can be accompanied by presence of various antiphospholipid antibodies (aPL). The laboratory criteria of antiphospholipid syndrome are based on detection of anticardiolipin, lupus anticoagulant or to antiβ2- glycoprotein I but currently a significance of other multiple aPL is being discussed. Because of their vascular and neuroinflammatory effect aPL, if being transplacentally transferred, might inflict damage in developing organism. The aim of our study was to determine the occurrence of eight selected aPL in offspring of mothers with proven autoimmune disease with aPL positivity. The possible influence of aPL presence on clinical, ultrasound and laboratory outcome of children was observed as well. The prospective study included 38 women: 17 women with primary antiphospholipid syndrome and 21 women with other diagnosed autoimmune disease with detected aPL. Also included were 39 children born to the above mentioned mothers between January 2009 and April 2010 in Perinatology Centre in Pilsen, Czech Republic. The control group consisted of 30 mothers without AD and their 30 healthy singletons. Preliminary results of the study showed the presence of aPL in 42.1% neonates of aPL positive mothers with autoimmune disease, six month later aPL were present in only 37.5 % of these children. Observed occurrence of aPL positivity at 6 months of age in originally negative offspring could be attributed to vaccination or food exposure. Psychomotor development of children has proceeded without major deviations. The follow-up study continues and will evaluate both groups of children at two years of age.
Keywords: novorozenec; Infant, Newborn; zdravotní stav; Infant; autoimunitní nemoci; Humans; Case-Control Studies; Pregnancy; kojenec; studie případů a kontrol; Female; mladý dospělý; dospělí; antifosfolipidové protilátky; lidé; Pregnancy Complications; Autoimmune Diseases; Adult; vývoj dítěte; ženské pohlaví; Health Status; Child Development; těhotenství; Antibodies, Antiphospholipid; Young Adult; komplikace těhotenství; prospektivní studie; Prospective Studies